Perceptions towards Credit Card Usage: Factor Analytic Finding from Pakistan - Siddiqui, Kamran; Anjum, Mahwish (International Journal of Economics, Business and Management Studies, 2013)
This paper aims to present the individual differences among credit card users with reference to their age and Sex. Data for the research were collected through a survey of customers of Credit Card users in Pakistan. The results show that some age and Sex differences exist in the credit card usage. The research focuses on credit card services in Pakistan; further research from dispersed geographic areas may be necessary before generalization can be made on the entire service industry. Service providers can use this model for their market segmentation and targeting activities leading to better positioning their products/services in the competitive banking services. Although there are studies on individual differences of services; research on individual differences on credit cards is very limited; this research adds significant value on the subject area.